FDA-ARGOS is a database with public quality-controlled reference genomes for diagnostic use and regulatory science - Heike Sichtig (Nature Portfolio, 2019)
To be able to use infectious disease next generation sequencing as a diagnostic tool, appropriate reference datasets are required. Here, Sichtig et al. describe FDA-ARGOS, a reference database for high-quality microbial reference genomes, and demonstrate its utility on the example of two use cases.